Analysis of Social Media Utilization by Students in Higher Education: A Critical Literature Review of Ghana - Demuyakor, John (Journal of New Media and Mass Communication, 2020)
Social media has drastically changed the communication perspective of the world through different aspects, both positively and negatively. The existence of social media has made it easy for scholars and non-scholars to pass information in the form of communication as well as has boosted businesses through online advertising and selling. Social media is enhanced by different aspects and forms of technology hence it is safe to say the two go hand in hand in depicting a social and now our academic world. Social media and Institutions of Higher Education work together to explore different skills including critical thinking, collaborations, and knowledge construction. This means that students, lecturers, and professors benefit differently from social media. For instance, in certain countries, social media is accepted as a tool for teaching and learning. Ideally, through social media, one is able to attend online classes without necessarily appearing physically at the lecture hall. In a country like Ghana, social media has paved ways to very many teachers and students in higher educational institutions who have benefited differently. This paper focuses on a literature review of social media utilization by students in higher educational institutions in Ghana. Other concepts of social media will also be explored including the positive and negative effects of social media on students and professors in tertiary education.